(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The hepatitis B virus is a global public health concern and leading cause of chronic liver disease in Bangladesh. For the diagnosis and monitoring of treatment of Hepatitis B virus infection, HBV-DNA detection and quantification is now extensively used worldwide. Objectives: The objective of this study was to detect HBV-DNA by real time PCR method in HBsAg positive patients, to compare the results of HBVDNA detection with HBeAg and Anti-HBe and to monitor the response after antiviral therapy in chronic hepatitis B patients and also to observe the intensity of hepatitis B infection in relation to age and sex. Methods: This was a cross sectional type of study conducted in Armed Forces Institute of Pathology (AFIP), Dhaka Cantonment. In this study, 56 sera of HBsAg positive patients were selected who all were subjected to do HBV-DNA (real time PCR) analysis during the period of 29 July to 30 0ctober, 2013. Results: Out of 56 HBsAg positive patients, HBV-DNA was detected in 34 patients. Among these, 8 (23.5%) patients were HBeAg positive, 16 (47%) patients were anti-HBe positive and 10 (29.5%) were negative for both HBeAg and anti-HBe. Age limit of patients was up to 60 years. HBV-DNA positive patients showed male predominance; 26 (76.5%) patients were male and 8 (23.5%) patients were female. Mean age of the patients was 35±14 years. Among 56 HBsAg positive patients, fifteen were receiving antiviral therapy. Out of them, HBV-DNA was decreased among 4 patients and could not be detected among 11 patients. Conclusion: Real time PCR method of detection of HBV-DNA is very important in patients who are HBeAg negative and this method is also applied to monitor treatment response to antivirals and to detect occult HBV infections immune control phase and also to detect reactivation of HBV cases. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014